Two Hundred Thirty-Six Children With Developmental Hydrocephalus: Causes and Clinical Consequences. (March 2016) - Tully, Hannah M.; Ishak, Gisele E.; Rue, Tessa C.; Dempsey, Jennifer C.; Browd, Samuel R.; Millen, Kathleen J.; Doherty, Dan; Dobyns, William B.
Few systematic assessments of developmental forms of hydrocephalus exist. We reviewed magnetic resonance images (MRIs) and clinical records of patients with infancy-onset hydrocephalus. Among 411 infants, 236 had hydrocephalus with no recognizable extrinsic cause. These children were assigned to 1 of 5 subtypes and compared on the basis of clinical characteristics and developmental and surgical outcomes. At an average age of 5.3 years, 72% of children were walking independently and 87% could eat by mouth; in addition, 18% had epilepsy. Distinct patterns of associated malformations and syndromes were observed within each subtype. On average, children with aqueductal obstruction, cysts, and encephaloceles had worse clinical outcomes than those with other forms of developmental hydrocephalus. Overall, 53% of surgically treated patients experienced at least 1 shunt failure, but hydrocephalus associated with posterior fossa crowding required fewer shunt revisions. We conclude that each subtype of developmental hydrocephalus is associated with distinct clinical characteristics, syndromology, and outcomes, suggesting differences in underlying mechanisms.